PENENTUAN ISI AWAL MINYAK DI TEMPAT DENGAN METODE VOLUMETRIK DAN MATERIAL BALANCE GARIS LURUS HAVLENA-ODEH DAN PERKIRAAN PRODUKSI ZONA ENH PADA LAPANGAN X - Eoremila Ninetu Hartantyo; Lestari Said (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2016)
The purpose of this thesis is to calculate the original oil in place of ENH zone in X field. There are two methods to calculate the original oil in place of ENH zone, which is volumetric method and material balance method. From the calculation of original oil in place of ENH zone using volumetric method is 5.860.310 STB.In Havlena - Odeh straight line material balance method needs the number of water influx. The water influx can be determine using Van-Everdingen Hurst method. The constant number of water influx of ENH zone is 311 BBL/psia. The original oil in place calculation of ENH zone using material balance method is 6.000.000 STB. Decline curve analysis is a method to determine the production performance and estimate ultimate recovery (EUR). By knowing the economic limit rate of ENH zone at 40 BOPD, it can be searched the oil rate and cumulative oil production of ENH zone. The economic limit rate of ENH is reached in March 2019 with recovery factor at 57,95%.Keywords: original oil in place, volumetric, material balance, decline curve analysis